GENE DISCOVERY IN SCHIZOPHRENIA AND BIPOLAR DISORDER - Ayub, Muhammad; Blackwood, Douglas (Journal of Pakistan Psychiatric Society, 2008)
Over the past few years there have been encouraging advances identifying genetic risk factors in schizophrenia and bipolar disorder and these may be the first steps towards understanding the biology of the disorders leading to novel treatment and preventative strategies. Recently the pace of discovery has increased as new microarray and DNA sequencing technologies now make it possible to survey very large cohorts of patients using many DNA markers to identify some of the many common and rare genetic variants contributing to the disorders. Douglas Blackwood, professor of psychiatric genetics at the University of Edinburgh has been working with Dr Muhammad Ayub, carrying out genetic linkage studies with families from Pakistan with bipolar disorder and depression.